THE IMPACT OF DIGITAL TECHNOLOGY ON ATHLETIC PERFORMANCE: A REVIEW OF WEARABLE DEVICES AND SPORTS ANALYTICS - Shukla, Tushar Dhar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Digital technology has revolutionized the landscape of sports and athletic performance, offering unprecedented opportunities for athletes, coaches, and sports scientists to enhance performance, prevent injuries, and optimize training strategies. This review delves into the impact of digital technology, focusing on the integration of wearable devices and sports analytics in modern athletics. Wearable devices, ranging from fitness trackers to advanced biomechanical sensors, provide real-time data on various physiological and biomechanical parameters, allowing for personalized training regimens and immediate feedback. These devices monitor metrics such as heart rate, oxygen consumption, muscle activity, and movement patterns, enabling a detailed analysis of an athlete's performance and recovery. The rise of sports analytics, powered by big data and artificial intelligence, has further transformed the way athletic performance is evaluated and improved. Advanced algorithms analyse vast amounts of data generated by wearable devices and other sources, identifying patterns and correlations that were previously undetectable. This data-driven approach enables coaches and athletes to make informed decisions, tailor training programs, and predict performance outcomes with greater accuracy. Moreover, sports analytics has expanded beyond individual performance, offering insights into team dynamics, opponent strategies, and game tactics, thereby enhancing the overall competitiveness of sports. This review also explores the challenges and ethical considerations associated with the widespread adoption of digital technology in sports, including data privacy, the potential for over-reliance on technology, and the digital divide between technologically advanced and less-equipped athletes or teams. Despite these challenges, the benefits of integrating wearable devices and sports analytics in athletics are undeniable. As digital technology continues to evolve, its role in shaping the future of sports and athletic performance will only become more pronounced, paving the way for new levels of excellence and innovation in the field.